The evolution of complex hunter-gatherers in the North Pacific: An archaeological case study from Kodiak Island, Alaska. - Fitzhugh, J. Benjamin (1996)
This dissertation examines the evolution of complex hunter-gatherers in the North Pacific with an archaeological settlement study from the Kodiak Archipelago, Alaska. The central problem addressed concerns the evolution of inequality and rank. In particular, what in socio-cultural evolution compels some individuals to accept subordinate positions? This problem is examined using theory developed in evolutionary ecology, cultural ecology, and social action theory. A model is developed to account for the evolution of non-egalitarian hunter-gatherers that focuses on the interplay between environmental risk management, demography, and social competition. This model is then evaluated with a case study from the Sitkalidak Island region of Southeast Kodiak. Archaeological survey and sampling from a 400 km$\sp2$ area revealed 152 prehistoric and historic habitation and activity sites, from 7500 years ago (6600 $±$ 230bp) until AD 1950. These include small camps and special activity sites from all ages and large villages and defensive sites from the later prehistoric period, and indicate changing economic, social, political, and demographic circumstances during almost 8000 years. Twenty-nine radiocarbon dates suggest a gap in the archaeological sequence of this region from approximately 4000 to 1800 years ago. This gap is unparalleled in other areas of Kodiak, although sites of this period are uncommon. In addition, survey data (site elevations and locations) are used to evaluate a geomorphological model of tectonic uplift for this portion of Kodiak. The data show that Sitkalidak had an emerging coastline for most of the Holocene. Beyond the survey findings, four test excavations are described. The Tanginak Spring site (KOD 481) is currently one of the oldest sites identified in the Kodiak Archipelago. It contains one of the best lithic assemblages yet documented for the early Ocean Bay I phase on Kodiak. In addition, findings from the Bear Island Site (KOD 564), the Partition Cliff site (KOD 473), and the Old Harbor ...